A case of peripheral gangrene and osteomyelitis secondary to terlipressin therapy in advanced liver disease - Heon Ju Lee; Myung Jin Oh (Clinical and Molecular Hepatology, 2013)
Variceal bleeding and hepatorenal syndrome (HRS) are serious and life-threatening complications of advanced liver disease. Terlipressin is widely used to manage both acute variceal bleeding and HRS due to its potency and long duration of action. The most severe (though rare) adverse event is ischemia. The present report describes the case of a patient with gangrene and osteomyelitis secondary to terlipressin therapy. A 71-year-old male with alcoholic liver cirrhosis (Child-Pugh B) and chronic hepatitis C was admitted due to a drowsy mental status. The patient had several experiences of orthopedic surgery. His creatinine level had gradually elevated to 4.02 mg/dL, and his urine output decreased to 500 mL/24 hr. The patient was diagnosed as having grade III hepatic encephalopathy (HE) and type II HRS. Terlipressin and albumin were administered intravenously to treat the HRS over 11 days. Although he recovered from the HE and HRS, the patient developed peripheral gangrene and osteomyelitis in both feet. His right toes were cured with the aid of rescue therapy, but his left three toes had to be amputated. Peripheral gangrene and osteomyelitis secondary to terlipressin therapy occur only rarely, and there is no specific rescue therapy for these conditions. Thus, attention should be paid to the possibility of ischemia of the skin and bone during or after terlipressin therapy.